1993
DOI: 10.1007/bf00037281
|View full text |Cite
|
Sign up to set email alerts
|

Factors effecting adventitious shoot regeneration from leaf explants of quince (Cydonia oblonga)

Abstract: A procedure for adventitious shoot regeneration from leaf explants of quince (Cydonia oblonga Mill.) using thidiazuron (TDZ) was developed. Excised leaves of cultures grown on Murashige and Skoog (MS) medium containing 5 p~M benzyladenine (BA) and 0.9% Gibco Phytagar were used. Several experiments were conducted to determine optimum concentrations of thidiazuron, a-naphthaleneacetic acid (NAA) and sucrose. When the medium contained 1.5 txM TDZ and 2.5 ~M NAA, 85% of the discs regenerated shoots with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…In our study, when 40-day-old and other younger or older leaves were compared, it was clear that 40-day-old explants were much more productive for shoot formation than others. Similar studies have also been reported in Prunus (Mante et al 1989), Lachenalia (Niederwieser and Van Staden 1990), Cydonia oblonga (Baker and Bhatia 1993), Aegle marmelos (Islam et al 1993) and Malus (Famiani et al 1994).…”
Section: Plant Regeneration From Leaf Explantssupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, when 40-day-old and other younger or older leaves were compared, it was clear that 40-day-old explants were much more productive for shoot formation than others. Similar studies have also been reported in Prunus (Mante et al 1989), Lachenalia (Niederwieser and Van Staden 1990), Cydonia oblonga (Baker and Bhatia 1993), Aegle marmelos (Islam et al 1993) and Malus (Famiani et al 1994).…”
Section: Plant Regeneration From Leaf Explantssupporting
confidence: 79%
“…Prior incubation in the dark is very important process for dedifferentiation and differentiation of P. occidentalis. Incubation in the dark has been reported to increase shoot regeneration in various plant species, such as blueberry (Billings et al 1988), pear (Chevreau et al 1989), apple (Fasolo et al 1989), campanula (Sriskandarajah et al 2004), watermelon (Compton 1999), Zhanhua winter jujube (Gu and Zhang 2005) and quince (Baker and Bhatia 1993). Our results indicated that an incubation period of 7 days in the dark is optimal for shoot regeneration of P. occidentalis (data not presented).…”
Section: Plant Regeneration From Leaf Explantscontrasting
confidence: 69%
“…Explants from juvenile plants regenerate shoots more effectively than those from mature plants (Dong and Jia, 1991;Baker and Bhatia, 1993;Becerra et al, 2004;Zhang et al, 2015). The decline in shoot regeneration capacity with aging is at least partly due to a reduced responsiveness to plant hormones.…”
Section: Developmental Constraints That Impact Plant Regenerationmentioning
confidence: 99%
“…Our preliminary experiments indicated a difference in response between tissues pretreated in the dark, followed by culture under illumination versus those not receiving the dark pretreatment. Incubation in the dark also increases shoot regeneration in species such as blueberry (Billings et al, 1988), pear (Chevreau et al, 1989), apple (Fasolo et al, 1989), quince (Baker and Bhatia, 1993), and rose (Ibrahim and Debergh, 2001). Therefore, we conclude that incubating the tissue for 10 d in the dark is more effective for promoting shoot regeneration in H. orientalis.…”
Section: Discussionmentioning
confidence: 95%